1976
DOI: 10.1126/science.1257754
|View full text |Cite
|
Sign up to set email alerts
|

Sex Pheromone Specificity in the Pine Sawflies: Interchange of Acid Moieties in an Ester

Abstract: 3,7-Dimethylpentadecan-2-ol was identified as the free alcohol in three species from two genera of pine sawflies (Hymenoptera: Diprionidae). In Neodiprion lecontei and Neodiprion sertifer the acetate of this alcohol is the major component of their sex attractant; in Diprion similis it is the propionate. By examining the responses of the male antennae of several species of Neodiprion through the electroantennographic technique, it was determined that four species responded to the acetate and six to the propiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…The stereochemically pure starting compounds, (2R,3S)-and (2S,3S)-2-methyl-3-hydroxybutanoic acid (4), were derived from optically pure 3-hydroxybutanoic acid. 1 These results indicate the importance of the (7 S)-methyl group to the function of tA as the main pheromone at low doses. However, it was also confirmed that (2S,3S)-2A could take the place of (2S,3S, 7 S)-IA at high doses.…”
Section: Resultsmentioning
confidence: 62%
“…The stereochemically pure starting compounds, (2R,3S)-and (2S,3S)-2-methyl-3-hydroxybutanoic acid (4), were derived from optically pure 3-hydroxybutanoic acid. 1 These results indicate the importance of the (7 S)-methyl group to the function of tA as the main pheromone at low doses. However, it was also confirmed that (2S,3S)-2A could take the place of (2S,3S, 7 S)-IA at high doses.…”
Section: Resultsmentioning
confidence: 62%
“…Recently its presence was also confirmed in Cephalcia abietis (Linné, 1758), too (GRUPPE, NISSLEIN 1996). In some species the presence of sex pheromone was observed in both laboratory and field tests (COP-PEL et al 1960;JEWETT et al 1976;LÖFQVIST 1986;OLAIFA et al 1987OLAIFA et al , 1988. There is a possibility of sex pheromone existence in other sawflies.…”
Section: Discussionmentioning
confidence: 91%
“…For example, since peak d elutes very nearly at the same temperature as a C26 ester and its fatty acid moieties have 18, 20 and/or 22 carbons, the alcohol moieties if primary can only have 8, 6 or 4 carbons. In vivo very short acid moieties of long chain esters have been reported a number of times; for example, esters of acetic and propionic acids serve as sex pheromones in pine sawflies (15), of acetic, acetoacetic and hydroxybutyric acids are present in the cuticle wax of tobacco hornworm pupae (5), of acetic acid occur in the leaf wax of the dicotyledon Chenopodium album (1), and of C2, 5, 7 and 8 acids are found in the surface wax of the crustacean Ligia oceanica (9). Interestingly, in the latter long chain esters of C5, 6 and 7 primary alcohols have also been reported.…”
Section: Isolation Of Labelled Esters and Their Identificationmentioning
confidence: 99%